2017
DOI: 10.1039/c7ra07983d
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydrophobic alkyl chain length on the mechanical properties of latex particle hydrogels

Abstract: The hydrogels with optimal alkyl segments reinforced by LPs exhibited the maximum fracture stress of 1.2 MPa and elongation of 2336%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 35 publications
(33 reference statements)
3
34
0
Order By: Relevance
“…In addition to these studies, they investigated the effect of hydrophobic alkyl chain length on the mechanical properties of the hydrophobically-associated hydrogels. Gao 25 selected different long alkyl chains as segments to enhance the performance of the hydrophobicallyassociated hydrogels with the PBA latex particles as the crosslinking centers. Hence, the long alkyl chains could effectively entangle with the PBA latex particles through strong hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these studies, they investigated the effect of hydrophobic alkyl chain length on the mechanical properties of the hydrophobically-associated hydrogels. Gao 25 selected different long alkyl chains as segments to enhance the performance of the hydrophobicallyassociated hydrogels with the PBA latex particles as the crosslinking centers. Hence, the long alkyl chains could effectively entangle with the PBA latex particles through strong hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophobic groups can play a role in protection of hydantoin group from water or other harmful molecules in destabilizing N-Cl with alkyl long chain. [57,58] The PEO group can be considered as sacrificial groups by absorbing deactivation agent of N-Cl such as water molecule from the environment. [59][60][61] 1 H-NMR spectra of each HD-TPU having decyne, PEO and PFO moiety indicate successful co-functionalization of HD-TPU via sequential click reaction (Figure 8).…”
Section: Multi-functionalization Of Hd-tpu To Improve Stabilitymentioning
confidence: 99%
“…Indeed, Gao et al showed that materials with a lower molecular weight have fewer entanglements, resulting in lower mechanical strength. 29…”
Section: Determination Of the Mechanical Properties Of The Crosslinkementioning
confidence: 99%